Generating English Language learners’ Interaction in an Online Learning Environment - Rizky Eka Prasetya (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The study aims to investigate and explore the characterization interaction in the English language online learning based on the English lecturers’ perspective. The quantitative descriptive survey approach is conducted for the study. It gathered measurable or quantifiable data to conduct statistical analysis. 74 English lecturers are respondents to the structured questionnaire. It is based on a five-point Likert-type rating scale with 19 items statements created using Google forms and sent to English lecturers digitally through e-mail and electronic messages. Based on the finding, the interaction characterization involved creating teaching, cognitive, and social presence, raising English language learning engagement and pleasure, improving English learners’ learning advancement, and increasing persistence and retention of English language learners. The mean of 15 of the 19 items was more prominent than 3.0, suggesting that respondents usually agreed. The following four questions had a mean larger than 2.5, suggesting that respondents were typically apprehensive about them. Additionally, the survey indicated that just 3.84 means dividing a complicated subject into manageable components. It is considered beneficial interaction in the online environment. This research has implications for the construction of online learning environments, the role of English lecturers in online courses, and educational support to help English language learners accommodate to more active engagement patterns in online learning settings